Robbery And Restitution : the Conflict over Jewish Property in Europe. - Dean, Martin (War and genocide., 2007)
The robbery and restitution of Jewish property are two inextricably linked social processes. It is not possible to understand the lawsuits and international agreements on the restoration of Jewish property of the late 1990s without examining what was robbed and by whom. In this volume distinguished historians first outline the mechanisms and scope of the European-wide program of plunder and then assess the effectiveness and historical implications of post-war restitution efforts. Everywhere the solution of legal and material problems was intertwined with changing national myths about the wa.